1995
DOI: 10.1074/jbc.270.42.24864
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Liposome-mediated Intravenous Gene Delivery

Abstract: Systemic gene transfer provides new opportunities for the analysis of gene function and gene regulation in vivo, as well as for human gene therapy. We used the chloramphenicol acetyltransferase reporter gene to examine several parameters important for the development of efficient, cationic liposome-mediated, intravenous (IV) gene transfer in mice. We then demonstrated that this approach can produce high level expression of biologically important genes. Specifically, we assessed the relationship of expression v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(125 citation statements)
references
References 31 publications
3
122
0
Order By: Relevance
“…41 This acquired response reduces the efficacy of repetitive administration of viral vectors. An advantage that cationic liposome-based lipoplexes possess over viral vectors is that they are less antigenic and therefore suitable for strategies requiring repeated injections 5,6,42 such as TAA therapy. Therefore, cationic liposome-based vectors or LPD might be effective in providing repeated boosts for specific tumor antigens since immunity would be raised against cells producing antigen, but not against the vector itself.…”
Section: Discussionmentioning
confidence: 99%
“…41 This acquired response reduces the efficacy of repetitive administration of viral vectors. An advantage that cationic liposome-based lipoplexes possess over viral vectors is that they are less antigenic and therefore suitable for strategies requiring repeated injections 5,6,42 such as TAA therapy. Therefore, cationic liposome-based vectors or LPD might be effective in providing repeated boosts for specific tumor antigens since immunity would be raised against cells producing antigen, but not against the vector itself.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting DNA vectors to cellular Tf receptors has been tried successfully before by linking the ligand to polycation conjugates (Liu et al, 1995;Zhu et al, 1993), through association of the protein with cationic liposomes and by covalent coupling of anti-Tf receptor monoclonal antibodies to the distal ends of PEG on sterically stabilized liposomes (Shi et al, 2001) or on nanoparticles (Olivier et al, 2002). In this regard, we and others have demonstrated that the association of human Tf to cationic liposome/DNA complexes enhances transfection in a large variety of cells, including dividing and nondividing cells (Cheng, 1996;Simoes et al, 1998Simoes et al, , 1999b.…”
Section: Introductionmentioning
confidence: 99%
“…39 Plasmid DNA was prepared by the modified alkaline lysis procedure, followed by polyethylene glycol precipitation, as described previously. 40 Preparation of LDC Sterile 10 mM solutions of the cationic liposome DOTIM octadecenoyloxy(ethyl-2-heptadecenyl-3-hydroxyethyl) imidazolinium chloride and cholesterol were prepared in a 1:1 molar ratio as described previously, except that the liposomes were extruded through a final filter diameter of 200 nm rather than 100 nm. 41 LDC were formed just before injection by gently mixing cationic liposomes with plasmid DNA at a ratio of 16 nmol lipid per 1 mg DNA in 5% dextrose in water at room temperature.…”
Section: Plasmidsmentioning
confidence: 99%